2017
DOI: 10.1073/pnas.1703071114
|View full text |Cite
|
Sign up to set email alerts
|

Uncovering BRD4 hyperphosphorylation associated with cellular transformation in NUT midline carcinoma

Abstract: The epigenetic reader BRD4 plays a vital role in transcriptional regulation, cellular growth control, and cell-cycle progression. Dysregulation of BRD4 function has been implicated in the pathogenesis of a wide range of cancers. However, how BRD4 is regulated to maintain its normal function in healthy cells and how alteration of this process leads to cancer remain poorly understood. In this study, we discovered that BRD4 is hyperphosphorylated in NUT midline carcinoma and identified CDK9 as a potential kinase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
66
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 49 publications
(70 citation statements)
references
References 73 publications
1
66
0
1
Order By: Relevance
“…Phosphorylation of Brd4 is critical for its activation and also mediates alterations in its interactome. Brd4 hyperphosphorylation correlates with its oncogenic potential and increased phosphorylation levels lead to development of BET inhibitor resistance in certain types of cancer (46, 47). At present, casein kinase 2 (CK2) is the only protein kinase demonstrated to directly phosphorylate Brd4, although others have been shown to regulate Brd4 activity (35, 46, 48).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphorylation of Brd4 is critical for its activation and also mediates alterations in its interactome. Brd4 hyperphosphorylation correlates with its oncogenic potential and increased phosphorylation levels lead to development of BET inhibitor resistance in certain types of cancer (46, 47). At present, casein kinase 2 (CK2) is the only protein kinase demonstrated to directly phosphorylate Brd4, although others have been shown to regulate Brd4 activity (35, 46, 48).…”
Section: Discussionmentioning
confidence: 99%
“…Brd4 hyperphosphorylation correlates with its oncogenic potential and increased phosphorylation levels lead to development of BET inhibitor resistance in certain types of cancer (46, 47). At present, casein kinase 2 (CK2) is the only protein kinase demonstrated to directly phosphorylate Brd4, although others have been shown to regulate Brd4 activity (35, 46, 48). CK2 phosphorylation sites reside within the PDID domain, where phosphorylation results in a conformational change that unmasks the second bromodomain and enables interactions with acetyl-lysine residues (35).…”
Section: Discussionmentioning
confidence: 99%
“…The BRD4 gene is the best‐characterized member of the bromo‐ and extra‐terminal domain family of proteins and plays an important role in cellular growth control, cell cycle progression, and cancer development (Najafova et al, ; Wang et al, ). Houzelstein and coworkers (), studding a mouse model of the Brd4 gene, showed that the heterozygous mice displayed pre and postnatal growth defects associated with a reduced cell proliferation rate.…”
Section: Discussionmentioning
confidence: 99%
“…Une autre preuve du rôle de Brd4 dans la tumorigenèse est apparue à la suite de la découverte de formes de fusion entre Brd4 et NUT (nuclear protein in testis) dans la majorité des carcinomes de la ligne médiane 5 . Ces protéines de fusion assurent un remodelage de la chromatine et de la transcription nécessitant leur phosphorylation par cdk9 [42]. D'autres protéines de fusion responsables de transformation cellulaire et retrouvées dans environ 5 % des leucémies aiguës, aboutissent à la formation de complexes impliquant P-TEFb, induisant une transcription aberrante [43].…”
Section: Les Risques De Cibler Des Protéines Pléiotropiquesunclassified